2023
DOI: 10.1080/13546783.2023.2189163
|View full text |Cite
|
Sign up to set email alerts
|

Bullshit blind spots: the roles of miscalibration and information processing in bullshit detection

Abstract: The growing prevalence of misleading information (i.e., bullshit) in society carries with it an increased need to understand the processes underlying many people's susceptibility to falling for it. Here we report two studies (N = 412) examining the associations between one's ability to detect pseudo-profound bullshit, confidence in one's bullshit detection abilities, and the metacognitive experience of evaluating potentially misleading information. We find that people with the lowest (highest) bullshit detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…The results presented here reveal important differences in the extent to which reflective thinking can alter perceptions of various types of misleading information. Crucially, we found that engaging in explanatory reflection leads to a reduction in receptivity to pseudo-profound bullshit, which supports Rand's (2019, 2020) claims that bullshit receptivity is driven (at least partially) by a lack of engagement in reflective thinking (also see Littrell & Fugelsang, 2023). However, we found that engaging in an explanatory reflection task did not reduce receptivity to scientific bullshit or fake news, which conflicts with the argument made by Rand (2019, 2020).…”
Section: Not All Bullshit Is Alikesupporting
confidence: 87%
See 3 more Smart Citations
“…The results presented here reveal important differences in the extent to which reflective thinking can alter perceptions of various types of misleading information. Crucially, we found that engaging in explanatory reflection leads to a reduction in receptivity to pseudo-profound bullshit, which supports Rand's (2019, 2020) claims that bullshit receptivity is driven (at least partially) by a lack of engagement in reflective thinking (also see Littrell & Fugelsang, 2023). However, we found that engaging in an explanatory reflection task did not reduce receptivity to scientific bullshit or fake news, which conflicts with the argument made by Rand (2019, 2020).…”
Section: Not All Bullshit Is Alikesupporting
confidence: 87%
“…However, a growing body of work has called these assumptions into question (Blacksmith et al, 2019;Patel et al, 2019;Stupple et al, 2017), finding that correct responses on tasks traditionally believed to require analytic reflection often result instead from "smart intuition" (Bago & De Neys, 2019;Raoelison et al, 2020). Moreover, using both self-report and reaction time data, Littrell and Fugelsang (2023) found that many people who gave higher ratings to pseudo-profound bullshit reported engaging in slower, more error-prone rationalizing while others who were less receptive to bullshit statements reported relying on faster, intuition-like processes.…”
Section: The Limits Of Reflective Thinking As a Strategy Against Misi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Research on deceptive behaviors usually focuses on lying, which deals with the deliberate production of false information to obtain desired goals. Another research area dealing with deceptive communication that has burgeoned only recently refers to bullshit (BS) BS deals with information expressed with indifference for truth, meaning, or accuracy which is supposed to impress, persuade, or mislead others for individual advantages (Littrell & Fugelsang, 2023;Littrell et al, 2022). BS production (bullshitting [BS'ing]), in turn, is the intentional, goal-directed dissemination of this kind of misleading information.…”
Section: Introductionmentioning
confidence: 99%